2021
DOI: 10.1371/journal.pone.0252057
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone vs methylprednisolone high dose for Covid-19 pneumonia

Abstract: Background There is no effective therapy for the severe acute respiratory syndrome by coronavirus 2 (SARS-CoV2) responsible for the Coronavirus disease 2019 (Covid-19). To date, dexamethasone has shown a decrease in mortality in patients who require oxygen, especially those with invasive mechanical ventilation. However, it is unknown if another corticosteroid can be used, the optimal dose and its duration, to achieve a better clinical outcome. The objective of the study was to compare the differences in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
171
2
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(202 citation statements)
references
References 26 publications
8
171
2
7
Order By: Relevance
“…Cyclooxygenase inhibitors, antibiotics, corticosteroids and other anti-inflammatory therapies do mildly affect CRP as a side effect ( 35 , 36 ). However, these therapies needed several days in order to affect CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase inhibitors, antibiotics, corticosteroids and other anti-inflammatory therapies do mildly affect CRP as a side effect ( 35 , 36 ). However, these therapies needed several days in order to affect CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these positive results, recently some papers came out questioning the positive effects of high-dose glucocorticoids, either dexamethasone or methylprednisolone [ 34 – 36 ]. However, other studies supported the beneficial effects of an immediate blunting of hyperinflammation using high-dose glucocorticoids in terms of increased survival [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the timing of steroid administration, the appropriate duration, and doses of steroids are also unclear. Pinzon et al [ 29 ] reported that high-dose methylprednisolone for three days followed by oral prednisone for 14 days decreased recovery time and need for intensive care compared with 6 mg dexamethasone for 7 to 10 days. Mishra et al [ 27 ] pointed out that long-term steroid use for COVID-19 may cause adverse drug reactions such as thrombosis.…”
Section: Discussionmentioning
confidence: 99%